2015
DOI: 10.1538/expanim.14-0098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four-week feed restriction on toxicological parameters in beagle dogs

Abstract: This study was conducted to examine any changes caused by feed restriction in dogs to contribute to safety evaluation in toxicity studies. Two male 7-month-old beagle dogs/group were fed 300 (control), 150 (50% of control), or 70 g/animal of diet daily (23% of control) for 4 weeks. Effects of feed restriction, except for clinical signs, were noted depending on the feed dosage in almost all examinations. The principal outcomes were: decreased body weight and water consumption, ECG changes (decreased heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 19 publications
11
10
0
Order By: Relevance
“…Other significant findings observed in this study were similar to those reported previously (Morita et al, 2015;Takamatsu et al, 2015). The following results have thus been reproducibly observed in reduced food intake studies: a decrease in body weight; a decrease in the WBC count (especially the Neut count); decreases in the AST, LDH, and Ca levels; an increase in the CRE level; a decrease in the thymus weight; and mild atrophy in the thymus.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Other significant findings observed in this study were similar to those reported previously (Morita et al, 2015;Takamatsu et al, 2015). The following results have thus been reproducibly observed in reduced food intake studies: a decrease in body weight; a decrease in the WBC count (especially the Neut count); decreases in the AST, LDH, and Ca levels; an increase in the CRE level; a decrease in the thymus weight; and mild atrophy in the thymus.…”
Section: Discussionsupporting
confidence: 92%
“…The blood chemistry results showed a decrease in the ALP level, similar to previously reported findings (Morita et al, 2015;Takamatsu et al, 2015). In the present study, ALP isozymes were assayed to confirm which organs were affected by the reduced food intake.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations